2020
DOI: 10.1016/j.earscirev.2020.103174
|View full text |Cite
|
Sign up to set email alerts
|

Mantle heterogeneity through Zn systematics in oceanic basalts: Evidence for a deep carbon cycling

Abstract: Subduction at convergent margins introduces a range of sedimentary and crustal materials into the mantle, providing the most dominant form of heterogeneity in the source of oceanic basalts. Yet, the relationship between geochemical variability and lithologic heterogeneities in the Earth's mantle remains controversial. In this paper, we comprehensively review Zn, δ 66 Zn and Sr-Nd isotope systematics in near-primary basalts erupted at mid-ocean ridges (MORB) and ocean islands (OIB) to help constrain the nature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 111 publications
3
41
0
Order By: Relevance
“…Zinc isotopes may be fractionated during crystal‐melt differentiation involving olivines that are isotopically lighter than the melts (McCoy‐West et al, 2018; Sossi et al, 2015; Yang & Liu, 2019), but detectable fractionation (~0.1‰) only occurs at the very end of the differentiation sequence when MgO falls below 3 wt.% as observed in the Kilauea Iki lavas (Chen et al, 2013). The studied alkali basalts have near‐primary compositions (MgO = 8.7–12.2 wt.%) and have δ 66 Zn values above the trend of Kilauea Iki lavas (Chen et al, 2013) as well as of global OIBs (Beunon et al, 2020; Wang et al, 2017) (Figure 7a). There is also no visible correlation of δ 66 Zn or δ 26 Mg with indices of magmatic differentiation (e.g., Mg # and CaO, Figure 6; SiO 2 , not shown), which is consistent with a negligible influence of magmatic differentiation on Mg and Zn isotopic systematics of the alkali basalts.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Zinc isotopes may be fractionated during crystal‐melt differentiation involving olivines that are isotopically lighter than the melts (McCoy‐West et al, 2018; Sossi et al, 2015; Yang & Liu, 2019), but detectable fractionation (~0.1‰) only occurs at the very end of the differentiation sequence when MgO falls below 3 wt.% as observed in the Kilauea Iki lavas (Chen et al, 2013). The studied alkali basalts have near‐primary compositions (MgO = 8.7–12.2 wt.%) and have δ 66 Zn values above the trend of Kilauea Iki lavas (Chen et al, 2013) as well as of global OIBs (Beunon et al, 2020; Wang et al, 2017) (Figure 7a). There is also no visible correlation of δ 66 Zn or δ 26 Mg with indices of magmatic differentiation (e.g., Mg # and CaO, Figure 6; SiO 2 , not shown), which is consistent with a negligible influence of magmatic differentiation on Mg and Zn isotopic systematics of the alkali basalts.…”
Section: Discussionmentioning
confidence: 90%
“…(a) Relationship between δ 66 Zn and Zn concentrations. Data for OIBs are from Chen et al (2013), Wang et al (2017), and Beunon et al (2020). (b) Relationship between δ 26 Mg and δ 66 Zn.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marine carbonates have heavier Zn isotope compositions than the normal mantle (Figure 1). Accordingly, the high δ 66 Zn values of the East China basalts and OIB (Figure 4a) are ascribed to the involvement of recycled/subducted isotopically heavy carbonate materials in mantle sources (Beunon et al, 2020;Jin et al, 2020;Liu et al, 2016;. In fact, previous studies, based on DSDP Sites 294, 295, and ODP Site 801 near the Ryukyu and Mariana trenches, have suggested that marine sediments are dominated by abyssal pelagic clays rather than carbonates (Plank, 2014;Plank & Langmuir, 1998).…”
Section: Effect Of Subducted Sedimentmentioning
confidence: 83%
“…In contrast, mantle melting has only a limited effect on the Zn isotope compositions of residual peridotites (Sossi et al, 2018;. Therefore, Zn isotope compositions of basaltic magma are insensitive to melt extraction, as indicated by the MORB-like δ 66 Zn values of Kamchatka-Aleutian arc basalts and could be used to identify the incorporation of recycled crustal components in their mantle sources via subduction only if Δ 66 Zn subduted component-mantle (i.e., δ 66 Zn subduted component -δ 66 Zn mantle ) is >0.08‰ (Beunon et al, 2020). For instance, sedimentary carbonates (0.91 ± 0.24‰; Liu et al, 2017;Lv et al, 2018;Pichat et al, 2003;Sweere et al, 2018;X.…”
mentioning
confidence: 99%